Equity valuation: Eli Lilly and company - Furtado, Margarida Costa (2021)
The process of Corporate Valuation is crucial in the financial industry. This process plays an important role for several fields within the finance area, being essential for a well-functioning of a strong and healthy business. For the present project, we used the valuation process with the purpose to estimate the fair price of Eli Lilly’s shares for the 31st December 2020, comparing it with the market price of shares for the same date in order to understand if there are or not investment opportunities for the investors and thus, provide them an investment recommendation. During this document, we have applied two different methodologies: The Discounted Cash Flow approach which is a more subjective model based on assumptions, and the Multiples valuation approach which is a more direct and simpler model. The chosen company, Eli Lilly, represents an international pharmaceutical that develops and sells human pharmaceutical products. The company has been growing over years, having reported a 10% increase in revenues for the year 2020. Lilly is listed on Nasdaq and as of 31st December 2020, its shares were priced at $167,40 each. Using the FCFF model, we were able to achieve a value of $313,90 per share. Taking the conclusions based on the FCFF model, the model suggests that the share price for 31st December 2020 is undervalued. For that reason, our final recommendation is that the investors should buy the company’s shares.